Thermodynamic properties of fatty acid esters in some biodiesel fuels - Levterov, A.M.; Levterov, A.A. (Functional Materials, 2018)
The thermophysical properties of biodiesel fuel in the high-temperature gas phase are studied for thermodynamic calculations of the working processes of piston engines. In the article the method for obtaining approximate analytical expressions of thermodynamic functions has been offered. The review of published experimental and design data enabled forming a set of thermodynamic and thermochemical properties of twenty-two complex methyl and ethyl chemically bonded esters of eleven higher fatty acids in biodiesel fuels. Next, the problem of polynomial approximation of thermodynamic functions has been solved. The coefficients of the approximating polynomials of the thermodynamic properties of esters in the gas phase have been tabulated.